2010
DOI: 10.1063/1.3447884
|View full text |Cite
|
Sign up to set email alerts
|

Starting current of coaxial relative backward wave oscillator

Abstract: This paper is devoted to study the starting current of the coaxial relativistic backward wave oscillator ͑CRBWO͒ using a simple physical model that employs the eigenmodes of the enclosed resonant cavity and the external quality factor of the open cavity Q. The agreement between the theoretical and simulation results is presented. It is found that CRBWO is suffering from the mode competition during the startup of the oscillation due to the wide interaction region over the range of the longitudinal wavenumbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This is tentatively considered to be because of the merits of the quasi-resonating cavity. 4,9 It is shown in Fig. 19 that the application of the coaxial dual annular cathodes greatly reduces the diode impedance.…”
Section: Numerical Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is tentatively considered to be because of the merits of the quasi-resonating cavity. 4,9 It is shown in Fig. 19 that the application of the coaxial dual annular cathodes greatly reduces the diode impedance.…”
Section: Numerical Analysis and Resultsmentioning
confidence: 99%
“…However, in the coaxial SWS, both the fundamental and the -1st harmonic branches of the quasi-TEM mode lie in the slow-wave region. 9 Thus, an electron beam with kinetic energy that is too high will deviate seriously from the π point of the quasi-TEM mode, as shown in Fig. 4, which indicates that the electron beams with energies of 700 keV and 800 keV are apparently far from the π point.…”
Section: A Dispersion Relationmentioning
confidence: 98%
“…Therefore, it is suggested that the resonant reflector with low external quality factor Q (≤10) should be chosen to minimize the unavoidable increase of electric field in the reflector region (Gunin et al, 1998a). In the hot dispersion shown in Figure 12, the structure wave and the slower space charge wave merge into a complex conjugate pair of solution whose imaginary part represents the temporal growth rate in the range of β 0 p from 0 to π (Teng et al, 2010). The ripple period and the ripple depth are p = 16 mm and d = 2 mm, respectively.…”
Section: Application Of Resonant Reflectormentioning
confidence: 99%
“…10 The mode competition unfavorably affects the wavebeam interaction and results in the generation with the impure spectrum consisting of several frequency components. 11 Furthermore, the generated power in the overmoded SWS always partly leaks into the diode region. This disturbs the explosive emission and the transmission of the electron beam.…”
Section: Introductionmentioning
confidence: 99%